Border regions, migration and place-making: The case of Trás-os-Montes in Portugal - Desille,Amandine (2022)
Abstract This contribution focuses on the implications of an enquiry on return migration in a border region. The northeastern region of Trás-os-Montes in Portugal is a paradigmatic area of out-migration, from colonial migrations to the ones to western and northern Europe during the Estado Novo, and the more recent migrations post-2008 crisis. The area went through dramatic demographic losses, accounting for a third of its population between the 1960s and 2000s. But it is also one of the areas with the highest rate of new residents - many of them coming (back) from France. The back and forth of inhabitants is only one form of mobilities in the history of the peninsula: as a border region, Trás-os-Montes is recently revisiting its transcultural heritage, such as the one of the Sephardic Jewish community, the Mirandese minority and more. Enquiring at the border hence holds many meanings, both in time and space, and both for those who stay and those mobile. Based on Pratt (1991) or Cohen & Sheringham (2017)'s understanding of “contact zones”, I explore the dynamics of place production in such a cultural space of encounters, conflicts, and renewal between several communities, in a region which has historically functioned as a transitional space. The theoretical reflection is accompanied by preliminary results of an ethnographic fieldwork conducted between 2018 and 2020 in the region. The case study of a village embedded in various networks, through out-migration and return migration, shows the extent to which the regional efforts to promote the area as “open to the outside” deny the potential of Portuguese migrants and returnees as active place-makers.